Banking Reform. Surveillance of Prudential Banking Financial Activities - Carmen Adriana Gheorghe (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2020)
The rules of prudential supervision have brought more success to the efficiency of banking, which is protected from practices that could be harmful. The regulations contained in the rules applicable to the systemic ensemble are recognized in the supervision through the legal relationship between the supervisory authority and the credit institution. Through the legally established principles, the National Bank of Romania develops the potential requirements imposed on credit institutions and establishes regular reporting in the conduct of the supervisory activity. All credit institutions have an obligation to draw up their own regulations, rules to be complied with and operations to be carried out only after communicating them to the supervisory authority.